2021
DOI: 10.3390/brainsci11111407
|View full text |Cite
|
Sign up to set email alerts
|

“I Feel Therefore I Decide”: Effect of Negative Emotions on Temporal Discounting and Probability Discounting

Abstract: Temporal and probability discounting are considered two fundamental constructs in economic science, as they are associated with phenomena with major societal impact and a variety of sub-optimal behaviors and clinical conditions. Although it is well known that positive and negative affective states bear important cognitive/behavioral consequences, the effect of emotional experiences on decision-making remains unclear due to the existence of many conflicting results. Inspired by the need to understand if and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 125 publications
(139 reference statements)
0
6
1
Order By: Relevance
“…Additionally, Calluso et al . ( 2021 ) found a negative correlation between compliance with containment measures and intertemporal discounting. As such, the following sections will further explore these factors in detail.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, Calluso et al . ( 2021 ) found a negative correlation between compliance with containment measures and intertemporal discounting. As such, the following sections will further explore these factors in detail.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, research has indicated that in financial decision-making, the degree of social distancing, but not mask use, was statistically significantly correlated with discount rates (Agrawal et al ., 2023 ). Studies have indicated that individuals who adhered to containment regulations more strictly were more likely to prefer immediate rewards in the intertemporal choice task (Calluso et al ., 2021 ; Lloyd et al ., 2021 ). This could be attributed to the desire for freedom that could only be enjoyed in the present (Calluso et al ., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These decision biases have been reproduced at a shorter time scale in the laboratory, using newspaper reports or small gifts to induce mood changes 6 8 . Although comparisons between groups using a single mood-inducing stimulus yielded mixed evidence 9 11 , comparisons between episodes created with different inductions showed that participants were generally more prone to take risks when in a good mood, and avoid risks when in a bad mood 12 15 . These effects qualify as decision biases because choice outcomes are independent from the events that triggered mood changes (e.g., lottery outcomes are independent from sport events).…”
Section: Introductionmentioning
confidence: 95%